Function of cGMP-dependent protein kinases that regulate molting in two decapod crustaceans, Gecarcinus lateralis and Carcinus maenas - Head, Talia, author; Mykles, Donald L., advisor; Sloan, Dan, committee member; Peers, Graham, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2025)
Physiological regulation of molting in decapods is predominantly coordinated by two hormones, the neuropeptide molt-inhibiting hormone (MIH), and steroid molting hormones termed ecdysteroids. MIH is produced and secreted by the X-organ/sinus gland complex located in the eyestalk ganglia and negatively regulates the production of ecdysteroids in the molting gland (Y-organ, YO). MIH signaling begins with a cAMP-dependent triggering phase followed by a cGMP-dependent summation phase which ultimately leads to inhibition of mTORC1-dependent ecdysteroid synthesis. The involvement of cGMP in MIH signaling implicates the activity of cGMP-dependent protein kinase (PKG), although the downstream effects of PKG remain unknown. The goal of this work was to phylogenetically characterize PKGs in crustaceans, characterize the physiological effects of PKG-inhibition on YO ecdysteroid synthesis, and identify potential substrates and downstream effects of MIH-dependent PKG activity in the YO. Two genes encoding PKG, pkg1 and pkg2, were identified in crustaceans and are conserved across metazoans. Alternative splicing of the PKG1 N-terminal region yields three PKG1α and one PKG1β isoform in crustaceans. PKG1 sequences with a 14- to 17- amino acid insertion within the kinase domain were identified in ten decapods and one stomatopod, and may indicate that alternative splicing occurs outside of the N-terminal region. In vitro assays of paired YOs incubated with MIH and PKG inhibitors were used to assess the effects of PKG activity on YO ecdysteroidogenesis in the European green shore crab, Carcinus maenas, and the blackback land crab, Gecarcinus lateralis. In the presence of MIH, inhibition of both PKG1 and PKG2 increased ecdysteroid synthesis relative to MIH alone, whereas PKG2 inhibition enhanced the effects of MIH. These data indicate that the two PKG isoforms have opposing roles in modulating ecdysteroidogenesis via MIH signaling in YOs. Specifically, PKG1 plays a dominant role in MIH signaling by inhibiting ecdysteroid synthesis, while PKG2 counters that inhibition and maintains basal ecdysteroidogenesis in the intermolt YO. Transcriptomic analysis of the PKG isoforms expressed in the YO in both G. lateralis and C. maenas suggest that PKG1α2 may be the dominant isoform expressed in the YO. Transcriptomic expression of PKG2 is dramatically reduced at each point in the molt cycle relative to PKG1 expression. Differential expression of the two kinases may explain how MIH signaling balances ecdysteroid inhibition while maintaining the basal secretion needed for peripheral metabolism during intermolt. Liquid chromatography/tandem mass spectrometry analysis of phosphopeptides enriched from PKG-inhibited YOs from C. maenas and G. lateralis revealed several novel potential substrates of PKG in the YO. Phosphopeptides were identified from proteins that regulate cytoskeletal organization, regulators of transcription and translation, and signaling pathways associated with growth factors and inhibition of the mechanistic target of rapamycin complex 1 (mTORC1). Together, these data indicate that PKG signaling in the YO is isoform-dependent, and may regulate ecdysteroidogenesis by interacting with multiple signaling pathways.
Keywords: decapod; molt-inhibiting hormone; Y-organ; ecdysteroid; cGMP-dependent protein kinase; molting